2010
DOI: 10.1074/jbc.m110.115089
|View full text |Cite
|
Sign up to set email alerts
|

Nedd4-1 and β-Arrestin-1 Are Key Regulators of Na+/H+ Exchanger 1 Ubiquitylation, Endocytosis, and Function

Abstract: The ubiquitously expressed mammalian Na ؉ /H ؉ exchanger 1 (NHE1) controls cell volume and pH but is also critically involved in complex biological processes like cell adhesion, cell migration, cell proliferation, and mechanosensation. Pathways controlling NHE1 turnover at the plasma membrane, however, are currently unclear. Here, we demonstrate that NHE1 undergoes ubiquitylation at the plasma membrane by a process that is unprecedented for a mammalian ion transport protein. This process requires the adapter p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 47 publications
3
52
0
1
Order By: Relevance
“…On the other hand, the interaction between Nedd4-2 and ratNHE3 was not only surprising but conflicted with our hypothesis that the PY motif in hNHE3 governs Nedd4-2 interaction. It is noteworthy that previous studies have shown interaction with Nedd4 proteins in the absence of PY motifs (29,35,36). In the cases of NHE1 and ␤ 2 -adrenergic receptor, ubiquitination and protein internalization by Nedd4-1 are mediated by the adaptor protein ␤-arrestin (29).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the interaction between Nedd4-2 and ratNHE3 was not only surprising but conflicted with our hypothesis that the PY motif in hNHE3 governs Nedd4-2 interaction. It is noteworthy that previous studies have shown interaction with Nedd4 proteins in the absence of PY motifs (29,35,36). In the cases of NHE1 and ␤ 2 -adrenergic receptor, ubiquitination and protein internalization by Nedd4-1 are mediated by the adaptor protein ␤-arrestin (29).…”
Section: Discussionmentioning
confidence: 99%
“…Dilutions of the total and surface NHE3 were resolved by SDS-PAGE and immunoblotted with an anti-VSVG antibody. Sequential cell surface biotinylation and immunoprecipitation were performed using monomeric avidin-agarose beads (Pierce), which allow elution of biotinylated proteins by excess free biotin as described (29). Densitometric analysis was performed using ImageJ software (National Institutes of Health).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…NHE1 abundance at the plasma membrane was recently shown to be regulated by direct ubiquitylation of the exchanger [154].…”
Section: Slc9a1-nhe1mentioning
confidence: 99%
“…NHE1 turnover at the plasma membrane is controlled by C-terminal ubiquitination, which targets the exchanger for endocytosis. 103 Factors influencing activation of NHE1 include phos-phorylation and interaction with regulatory molecules. For example, binding to calmodulin, a protein whose activation is dependent on intracellular Ca 2+ levels, activates NHE1.…”
Section: Mechanisms Controlling Nhe1 Activity and Expression In Pasmcmentioning
confidence: 99%